Biogenic amines in fermented foods - Sandra Torriani (Frontiers Research Topics, 2015)
Biogenic amines (BA) are sources of nitrogen and precursors for synthesis of hormones, alkaloids, nucleic acids and proteins, occurring in all organisms. Under normal condition in humans the consumption of food or beverages containing these compounds have not toxic effects because they are rapidly detoxified by the activity of the amine oxidizing enzymes, monoamine (MAO) and diamine oxidases (DAO). However in presence of high BA content, in allergic individuals or if MAO inhibitors are applied the detoxification system is not capable of metabolizing dietary intake of BA. This fact can induce toxicological risks and health troubles, but the European Union established regulation for just only histamine levels in fish and fishery products. The presence of BA in foods is due to the enzymatic decarboxylation of free amino acids by microorganisms that possess this activity. Many foods such as meat products, cheeses, fishes, fermented products and beverages could contain high levels of these compounds. Determination of BA rates in food are important as indicators of the degree of freshness or spoilage other then from the point of view of their toxicology. The content of the E-Book deals the presence of BA in some fermented and non fermented foods and the measures to control their content.